Thoughts on science popularization of earthquake prevention and disaster reduction in public opinion hotspots - Di Yao; Weiyong Shen; Qi Chen; Xiaotong Xu (地震科学进展, 2023)
Science popularization work on earthquake prevention and disaster reduction should keep pace with the times, play a greater role in public opinion guidance, and take more responsibility in public opinion governance. In this paper we discuss that science popularization of earthquake prevention and disaster reduction plays an important role in guiding public opinion from two aspects. First, the hotspots of public opinion provide an opportunity for science popularization of earthquake prevention and disaster reduction. Second, the hotspots of public opinion provide contents for science popularization of earthquake prevention and disaster reduction. I put forward the public opinion guidance strategy of science popularization of earthquake prevention and disaster reduction from three aspects. First, reasonably set the science popularization agenda and take the initiative to guide public opinion; Second, consciously guide public opinion by means of new media communication technology; The third is to play a good “combination boxing” to form the greatest resultant force for public opinion guidance. In the hotspots of public opinion, we should actively do a good job of science popularization of earthquake prevention and disaster reduction, innovate communication forms and methods, skillfully set the agenda, cover the whole time and space, and participate in the whole society, build a benign public opinion field for the exchange of information between the government, the media and the public, enhance the public’s risk awareness and disaster prevention ability, and truly build a people’s defense line for risk prevention and control.